Pesan Dakwah Dalam Web Series: Analisis Semeotika Roland Barthes Dalam Channel Youtube B3E Production: Story Of Dira Episode 1-9 Edisi 2021 - Rika Handayani; Darul Ilmi (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2023)
Web series is a serial viewing format that is broadcast via web-based internet technology such as YouTube and Vimeo. Web Series have a broadcast concept that is similar to television shows, but Web Series are shorter in duration, have clearer storylines and conflicts and are not long-winded. A strong story makes the audience understand and become more involved in the story, so this media is often used to convey preaching messages. Like one of the Web Series entitled "Story Of Dira" belonging to the B3E Production Youtube Channel. Various series that have been produced have achieved success, both in Indonesia and abroad. One of the achievements of the film When Hafidz Falls in Love was winning awards as favorite film and best director at ISMEFEST, 1st place at KUA Fest 2020, Ministry of Religion of the Republic of Indonesia. The purpose of this study is to find out what da'wah messages are contained in the Web Series Story Of Dira. The type of research used by the author in analyzing the Story Of Dira web series is library research using a qualitative approach. The data was analyzed using Roland Barthes' semiotic analysis. The research results show that the Web Series Story Of Dira contains a da'wah message, namely the message of the aqidah da'wah conveyed in this Web Series is about faith in Allah, faith in qhada and qhadar. The message of sharia da'wah is about prohibitions on dating, covering one's private parts, marriage, ta'aruf. The message of moral preaching is about telling the truth, forgiving, helping each other, inviting people to study and loving animals. Where the preaching message above is analyzed based on Roland Barthes' semiotic analysis approach, namely by examining signs or symbols with the meaning of denotation, connotation and myth.